Exploring causal associations between interleukins, their receptors, and acute respiratory distress syndrome: a bidirectional-Mendelian Randomization study - Ma, Jia-wei; Tang, Ji-chun; Fang, Hong-zhi (Frontiers in Genetics, 2024)
BackgroundAcute Respiratory Distress Syndrome (ARDS) is a severe lung condition posing significant health risks. Observational studies have indicated a potential linkage between ARDS and various interleukins, such as Interleukin-8, −2, −6, and −1β. However, the causal relationships between specific interleukins, their receptors, and ARDS remain unclear.MethodsThis study employed bidirectional Mendelian Randomization (MR) to investigate the causal associations between 197 different interleukins, interleukin receptors, and ARDS. GWAS summary data for interleukins and their receptors were sourced from publicly available studies, while ARDS data were derived from the FinnGen database. Wald Ratio and Inverse Variance Weighted (IVW) methods were primarily utilized in the MR analyses. Reverse MR was also conducted to explore reverse causations.ResultsThe study identified significant causal relationships between several interleukins, their receptors and ARDS. Specifically, Interleukin-17 receptor D (IL-17RD) (OR = 0.67, 95%CI = 0.51–0.89, p = 0.006), Interleukin-22 receptor subunit alpha-1 (IL22RA-1) (OR = 1.45, 95%CI = 1.08–1.96, p = 0.014), Interleukin-20 receptor subunit alpha (IL20RA) (OR = 0.53, 95%CI = 0.32–0.89, p = 0.016), Interleukin-22 (IL-22) (OR = 3.60, 95%CI = 1.20–10.83, p = 0.022), Interleukin-23 receptor (IL-23R) (OR = 2.14, 95%CI = 1.10–4.17, p = 0.025), Single Ig IL-1-related receptor (SIGIRR) (OR = 1.22, 95%CI = 1.00–1.48, p = 0.047) showed notable associations with ARDS. No reverse causal relationships were found on results above, and neither heterogeneity nor pleiotropy was detected in the analysis.ConclusionThis study elucidates the causal connections between specific interleukins, their receptors and ARDS, contributing significantly to the understanding of ARDS pathogenesis. These findings offer a foundation for further research and potential therapeutic interventions targeting these interleukins and receptors in ARDS management. The absence of reverse causation and pleiotropy, heterogeneity reinforces the robustness of these associations.